Consequences of not Working Sixteen Months After a Plant Closing - Burke, Ronald (Relations industrielles / Industrial Relations, 1985)
This paper examines the consequences of being unemployed sixteen months after the closing ofthe Canadian Admiral plant in Cambridge, Ontario in November 1981.